PERAN KEPUASAN KONSUMEN MEMEDIASI PENGARUH KUALITAS PELAYANAN DAN CITRA MEREK TERHADAP POSITIVE WORD OF MOUTH - Punkyanti, Ni Putu Dema; Seminari, Ni Ketut (E-Jurnal Manajemen; Vol 9 No 5 (2020)DO - 10.24843/EJMUNUD.2020.v09.i05.p19, 2020)
This study aims to determine the effe s ct of service quality, and brand image on positive word of mouth through customer satisfaction as a mediating variable. This research was conducted on Samsung Smartphone Consumers in Denpasar City, using Non-Probability Sampling techniques, as many as 100 respondents. Data collection was obtained from the distribution of questionnaires. Data analysis techniques used are path analysis and multiple test. The results showed that service quality had a positive and significant effect on positive word of mouth, brand image had a positive and significant effect on positive word of mouth, service quality had a positive and significant effect on customer satisfaction, brand image had a positive and significant effect on customer satisfaction, customer satisfaction positive and significant effect on positive word of mouth, the role of customer satisfaction mediates positively and significantly the relationship of service quality to positive word of mouth, and the role of consumer satisfaction positively and significantly relationship brand image to positive word of mouth. Keywords: brand image, customer satisfaction, service quality, positive word of mouth